Effect of air, anesthetic gas mixture, saline, or 2% lignocaine used for tracheal tube cuff inflation on coughing and laryngotracheal morbidity after tracheal extubation - Lokvendra S Budania; Vamsidhar Chamala; Madhu Rao; Samarth Virmani; Kush A Goyal; Kanika Nanda (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Coughing and sore throat postoperatively are common clinical problems during general anesthesia which can be avoided by various methods including topicalization of airway with local anesthetics, endotracheal tube cuff (ETT) inflation with local anesthetics, use of intravenous drugs such as dexamethasone, maintaining ETT cuff pressure, intubation by an experienced anethesiologist, etc. The aims of the study were to compare postextubation coughing response, mean number of cuff deflations required intraoperatively, and postoperative airway morbidity in terms of sore throat (2 h and 18-24 h), hoarseness of voice, and dysphagia following inflation of ETT cuff with air, anesthetic gas mixture, saline, and 2% lignocaine during general anesthesia. Material and Methods: One hundred and four patients were randomized into 1 of 4 groups depending on whether air, anesthetic gas mixture, saline, or 2% lignocaine was used to inflate the cuff of ETT using computer-generated randomization table. Results: There was no significant difference in the postextubation cough response among the four groups. The mean number of times the ETT cuff was deflated was significantly in favor of liquid media comapred to gaseous media (P < 0.001). The incidence of sore throat at 2 h and at 18-24 h, hoarseness of voice, and dysphagia were comparable in all groups. Conclusion: ETT cuff inflation with air, anesthetic gas mixture, 2% lignocaine, and saline are comparable in terms of incidence of postextubation cough and postoperative airway morbidity symptoms such as sore throat, hoarseness of voice, and dysphagia.